Фактори розвитку та напрями вдосконалення дистанційної форми навчання в системі вищої освіти України - Романовський, Олександр Георгійович; Квасник, Ольга Віталіївна; Мороз, Володимир Михайлович; Підбуцька, Ніна Вікторівна; Резнік, Світлана Миколаївна; Черкашин, Андрій Іванович; Шаполова, Вікторія Валеріївна (My University, 2019)
Трансформаційні процеси в сучасному суспільстві викликають необхідність переорієнтації сучасної освіти та перерозподілу векторів її розвитку в площину дистанційного навчання. Закономірна зміна пріоритетів у перспективах розвитку вищої освіти спрямована на розширення кола користувачів та здобувачів освітніх та інформаційних ресурсів. Існуюча парадигма розвитку освіти, з огляду на постійні зміни характеристик середовища її функціонування, все частіше стає об'єктом трансформаційних перетворень свого змісту та структури. Рефлексія теоретико-методологічної моделі розбудови педагогічної наукової думки стає підґрунтям для перегляду місця та ролі інструментарію традиційних педагогічних технологій у забезпеченні процесу освітньої комунікації між суб'єктами та об'єктами освітньо-наукової діяльності. Реалізація потенціалів дистанційної форми навчання, так само як і підвищення рівня використання педагогами інформаційно-комунікативних технологій, потребує не тільки усвідомлення останніми переваг тих чи інших педагогічних технологій, але й готовності об'єктів освітньо-наукової діяльності до сприйняття визначеної до засвоєння інформації. З огляду на необхідність розширення інформаційно-аналітичного підґрунтя щодо перспектив використання дистанційної форми навчання в Україні, а також для визначення детермінант її розвитку, авторами публікації було розглянуто історичну ретроспективу становлення дистанційної форми навчання на міжнародному та національному рівнях, а також проведено анкетування здобувачів вищої освіти щодо сили прояву окремих з детермінант (факторів) розвитку дистанційної освіти в Україні. За результатами аналізу відповідей респондентів була оцінена значущість впливу деяких з факторів на динаміку розвитку дистанційної освіти в Україні, а саме: індивідуальних особливостей людини; відсутності на ринку освітніх послуг актуальних відповідно до попиту на ринку праці пропозицій щодо освітніх програм; недосконалості змісту, форм та технологій реалізації дистанційних курсів, а також нездатності закладів вищої освіти забезпечити ефективність реалізації навчальних програм; недосконалості інституціонального середовища щодо забезпечення організації дистанційної освіти; неготовності роботодавців та представників соціуму визнати еквівалентність отриманих у межах дистанційної освіти знань, умінь та навичок тим компетентностям, які можуть бути сформовані в межах традиційних форм навчання. Стаття містить результати аналізу тенденцій розвитку масових відкритих онлайн-курсів та огляд змісту нормативно-правового забезпечення щодо функціонування дистанційної освіти. У статті запропоновано авторську класифікацію основних переваг та недоліків впровадження освіти на відстані за такими основними видами: організаційно-педагогічний, інформаційно-технологічний та психологічний. Стаття містить узагальнення та висновки щодо предмету наукової уваги.

Transformational processes in modern society call for the reorientation of modern education and the redistribution of the vectors of its development into the distance learning sphere. The legislative change of priorities in the perspectives of higher education development is aimed at expanding the range of users and recipients of educational and information resources. The existing paradigm of educational development is increasingly becoming the object of transformational conversion of its content and structure, in view of the constant changes in the characteristics of its functioning environment. Reflection of the theoretical and methodological model of the pedagogical scientific thought development becomes the basis for reviewing the place and role of the traditional pedagogical technologies tools in ensuring the process of educational communication between the subjects and objects of educational and scientific activity. Realization of the distance learning potentials, as well as the level of increasing information and communication technologies usage by teachers, requires the awareness not only of the advantages of particular pedagogical technologies, but also the readiness of educational and scientific activity objects for the perception of the determined for assimilation of information. In view of the need to expand the information and analytical basis for the prospects of distance learning using in Ukraine, as well as to determine the determinants of its development, the authors of the publication considered the historical retrospective of becoming a distance learning at the international and national levels, and higher education applicants were questioned regarding the manifestation of some of the determinants (factors) of development of distance education in Ukraine. According to the analysis results of the respondents' answers, the importance of influence of some factors on the dynamics of distance education development in Ukraine was assessed, namely: individual characteristics of a person; the absence of relevant educational programs on the market for educational services relevant to the demand on the labor market; imperfect content, forms and technologies of distance learning courses, as well as the inability of higher education institutions to ensure the effectiveness of curriculum implementation; the imperfection of the institutional environment to ensure the organization of distance education; the unwillingness of employers and members of the society to recognize the equivalence of the knowledge, skills and competences acquired in distance education to those competences that can be formed within traditional forms of education. The article presents the results of the analysis of the trends of mass open online courses and an overview of the content of regulatory support for the functioning of distance education. The article presents the author's classification of the main advantages and disadvantages of implementing distance education by the following main types: organizational-pedagogical, information-technological and psychological. In addition, the article highlights the potential of using distance learning technologies to form leadership qualities in higher education applicants. The researches were conducted on the basis of the hierarchical design concept application, according which training and formation of specialists' leadership qualities is carried out at the conceptual, technological and subject realization level, and systematic approach by involving the subjects of learning in its distance form. The article contains generalizations and conclusions about the subject of scientific attention.
Development factors and directions for improving distance learning in the higher education system of Ukraine
Keywords: дистанційна освіта; здобувачі вищої освіти; масові відкриті онлайн-курси; компетентність; навчання впродовж життя; споживачі освітніх послуг; distance education; applicants for higher education; massive open online courses; competence; life-long learning; leaders; consumers of educational services